RETRACTED: PAK5 facilitates the proliferation, invasion and migration in colorectal cancer cells - Silin Huang; Ying Zhu; Chunfei Wang; Xiaxi Li; Xiaobing Cui; Sufang Tu; Lijuan You; JingWen Fu; Zemin Chen; Wei Hu; Wei Gong (Cancer Medicine)
Abstract Colorectal cancer (CRC) is the third‐most common cancer around the world, accounting for approximately 10% of cancer‐related mortality. Deeper molecular understanding of colorectal carcinogenesis will provide evidences for identification of early diagnostic indicators and novel therapeutic strategies for CRC treatment. The p21cdc42/rac1‐activated kinase 5 (PAK5) has been reported to be involved in a variety of tumor‐promoting behaviors, whereas the underlying mechanisms of PAK5 in CRC progression are still obscure. Our current study revealed an upregulated expression of PAK5 in human CRC tissues as compared with normal adjacent biopsies, which was associated with tumor progression and metastasis. We further unraveled that inhibition of PAK5 was correlated with restrained proliferation, migration, and invasion of CRC cells in vitro and in vivo. Moreover, we showed an indispensable role of PAK5 in interacting with Cdc42 and Integrin β1, β3, thus, to facilitate the migration and invasion of CRC cells. Collectively, we pointed out a potential of PAK5 to serve as a novel therapeutic target in restricting CRC proliferation and metastasis. The uncovered mechanisms will deepen the comprehension with regard to the mechanisms of CRC progression, as well as providing new insights for therapeutic intervention in colorectal cancer.